Hybrid CFRP-based strengthening technique to increase the flexural resistance and concrete confinement of RC columns submitted to axial and cyclic lateral loading - Barros, Joaquim A. O. (2008)
A strengthening technique that combines carbon fibre reinforced polymer (CFRP) laminates and strips of wet lay-up CFRP sheet was used to increase the flexural resistance and the energy dissipation capacity of square cross-section columns of very low concrete strength submitted to constant axial compressive force and cyclic lateral loading. The laminates, applied according to the Near Surface Mounted (NSM) technique, have the purpose of increasing the flexural resistance of the columns, while the CFRP sheet installed as a localized jacket in the plastic hinge has the aim of increasing the concrete confinement and avoid the buckling and the debonding of the laminates. In spite of the 8 MPa of average concrete compressive strength used to manufacture the columns, the hybrid strategy provided an average increase of about 46 % in terms of load carrying capacity, even when applied in columns that had already been tested and presented intensives damages. The experimental program is described and the main results are presented and analyzed.